Interdisciplinary Applications of Kinematics Proceedings of the Third International Conference (IAK) - Kecskeméthy, Andrés; Geu Flores, Francisco; Carrera, Eliodoro; Elias, Dante A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the proceedings of the Third Conference on Interdisciplinary Applications of Kinematics (IAK 2018) held in Lima, Peru, March 5-7, 2018. The conference brought together scientists from several research fields, such as computational kinematics, multibody systems, industrial machines, robotics, biomechanics, mechatronics, computational chemistry, and vibration analysis, and embraced all key aspects of kinematics, namely, theoretical methods, modeling, optimization, experimental validation, industrial applications, and design. Kinematics is an exciting area of computational mechanics and plays a central role in a great variety of fields and industrial applications nowadays. Apart from research in pure kinematics, the field deals with problems of practical relevance that need to be solved in an interdisciplinary manner in order for new technologies to develop. The results presented in this book should be of interest for practicing and research engineers as well asPh.D. students from the fields of mechanical and electrical engineering, computer science, and computer graphics.
Optimal Lap Time for a Race Car -- The Influence of Axle Kinematics on Vehicle Dynamics -- Automotive Mechanisms for Improving Fuel Economy -- Detection of surface texture with an artificial tactile sensor -- Analysis of the dynamic behavior of beams supported by a visco‐elastic foundation in context to natural vibrissa -- Design of a cable‐based device for elbow rehabilitation and exercise -- Transoral Robotic Surgery (TORS) Emulaion Using a Highly Flexible Robotic System -- Characteristics of a Lower Limb Exoskeleton for Gait and Stair Climbing Therapies -- A 3D‐printed prosthetic hand with modular reconfigurable fingers -- Design and Analysis of a Lower Limb Exoskeleton for Rehabilitation -- A Method to Identify the Difference in Kinematic Behavior of Human Model Lower Extremities -- Modeling for the Design of a Lower Limb Exoskeleton for People with Gait Issues -- Human Modeling for Biomechanical Analysis of Closed Kinetic Chain Excercises of the Leg -- VDI 2742: Electronic Motion ControlSystems for Linkage Mechanisms: Principal Uses and Aspects of Realization -- MechDev - A new Software for Developing Planar Mechanisms -- Shaking Force Balance of the Peaucellier‐Lipkin Straight‐line Linkage -- The potential of the 7R‐R closed loop mechanism to transfer motion between 2 schafts with varying angular position -- Auxetic regions in large deformations of periodic frameworks -- Singularity analysis of a spherical robot used in upper limb rehabilitation -- Higher‐Order Kinematics of Rigid Bodies. A Tensors Algebra Approach -- Design of a solar powered mobile illumination tower with a solar tracker mechanism for increased efficiency -- Computational Tool for the Intelligent Design of Gearboxes of Cylindrical Gears and Welded Housing -- Compliant Mechanisms for Ultra‐precise Applications -- Modeling of the tilt sensitivity of a monolithic weighing cell structure -- Optimization of Compliant Mechanisms by Use of Different Polynomial Flexure Hinge Contours.
Keywords: Control engineering; Robotics; Automation; Mechanics, Applied; Statics; Control, Robotics, Automation; Engineering Mechanics; Mechanical Statics and Structures